2018
DOI: 10.1016/j.ophtha.2017.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraocular Lens Calculation Formulas

Abstract: Overall, the Barrett Universal II formula had the lowest prediction error for the 2 IOL models studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
444
8
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 503 publications
(511 citation statements)
references
References 14 publications
43
444
8
16
Order By: Relevance
“…14,17,31 We also performed the meta-analysis on the comparison of Olsen formula with Barrett Universal II and Haigis. 14,17,31 We also performed the meta-analysis on the comparison of Olsen formula with Barrett Universal II and Haigis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14,17,31 We also performed the meta-analysis on the comparison of Olsen formula with Barrett Universal II and Haigis. 14,17,31 We also performed the meta-analysis on the comparison of Olsen formula with Barrett Universal II and Haigis.…”
Section: Discussionmentioning
confidence: 99%
“…The newly developed Olsen formula showed potential advantages in predicting IOL power in eyes with long AL. 14,17,31 We also performed the meta-analysis on the comparison of Olsen formula with Barrett Universal II and Haigis. The results of the analysis showed that no statistical difference was observed in the comparison between Olsen and Barrett Universal II (Appendix A, I 2 = 0%, mean difference = 0.00D, P = 0.86), and between Olsen and Haigis (Appendix B, I 2 = 0%, mean difference = −0.02D, P = 0.14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations